Tindak Pidana Korupsi dalam Penyalahgunaan Dana Bergulir LPDB-KUKM oleh Koperasi PKL Jawa Barat Tahun 2012–2013 - Silalahi, Riamsah; Gultom, Potler; Sudarto, Sudarto (Neolectura, 2025)
This research focuses on the misuse of revolving fund loans/financing from the Cooperative Revolving Fund Management Institution, Micro, Small and Medium Enterprises (LPDB-KUKM) to the West Java Panca Bhakti Street Vendors Cooperative (Kopanti Jabar) in 2012 and 2013. Through a qualitative approach, this study identifies the modus operandi of the perpetrators, the impact of state losses, as well as the judge's consideration in handing down the verdict. The results showed that there were manipulations in the process of applying for and distributing funds, which resulted in state losses of Rp. 116,823,508,700.00. Judges consider aggravating and mitigating factors in imposing sentences, with the aim of providing a deterrent effect and recovering state losses. This research is expected to contribute to efforts to eradicate corruption in Indonesia.